Effects of Forestry Waste Neolamarckia cadamba Leaf Meal as an Additive on Fermentation Quality, Antioxidant Activity, and Bacterial Community of High-Moisture Stylo Silage - Wu, Shuo; Gao, Lin; Chen, Dandan; Xue, Yanlin; Kholif, Ahmed E.; Zhou, Wei; Chen, Xiaoyang; Zhang, Qing (Frontiers in Environmental Science, 2022)
Neolamarckia cadamba leaves, a byproduct of wood production, are always discarded in the field. N. cadamba leaves have strong antibacterial property, which might be recycled to inhibit undesirable bacteria and enhance fermentation quality of silage. Ensiling, a traditional conservation method for animal feed, is commonly used all over the world. It is common knowledge that high moisture forages, especially legumes, are difficult to ensile directly as much ammonia-N and butyric acid produced by undesirable bacteria will reduce the feeding value. To investigate the effects of N. cadamba leaves meal on fermentation quality of stylo silage, 5% and 10% N. cadamba leaves meal was mixed with stylo for 30 days of ensiling in two independent experiments. Results showed that silage pH and butyric acid content of stylo silage were decreased (P < 0.01) by 10% N. cadamba leaves meal. Contents of nonprotein-N and ammonia-N were significantly decreased (P < 0.05), while true protein content was significantly increased (P < 0.05). In addition, N. cadamba leaves meal addition also decreased the bacterial diversity. The relative abundance of Clostridium and Lelliottia decreased, whereas Lactobacillus increased when N. cadamba leaves meal was added. The above results suggested that mixing N. cadamba leaves meal to high moisture forages could be an effective strategy to enhance silage fermentation quality, and it is also a feasible way to recycle N. cadamba leaves.